The Effect of Entrepreneurship Education and Social Environment on The Intention to Start A Technology-Based Business Through Entrepreneurial Self-Efficacy - Iswanto, Huddy; F. Danardana Murwani; Hadi Sumarsono (International Journal of Technology and Education Research, 2025)
This study aims to analyze the influence of entrepreneurship education and social environment on technology-based entrepreneurial intentions through entrepreneurial self-efficacy in vocational high school students in Mojokerto Regency. The low level of technology-based entrepreneurship among students is caused by a lack of understanding, social environmental support, and effective entrepreneurial skills development. The approach used is quantitative with a survey method, using a questionnaire distributed to 198 respondents from four schools. Data analysis was carried out using descriptive and inferential statistics with the Partial Least Square (PLS) technique through SmartPLS software to test the relationship between variables. The results show that entrepreneurship education, social environment, and self-efficacy significantly and positively influence technology-based entrepreneurial intentions, and self-efficacy acts as a mediating variable. It is recommended that educators increase innovation in entrepreneurship learning and strengthen students' social support and digital competence to increase their interest and readiness in technology-based entrepreneurship